Pondok Pesantren dan Penanggulangan Narkoba di Indonesia - Nur Khamim (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2018)
Islamic boarding school has a function as an educational institution and propaganda and social institutions that have given the color of the area, especially rural areas. It is hoped that Islamic boarding schools are not only capable of fostering personal Muslim Islam, but also capable of making changes and improving social community. The influence of pesantren is very positive if the alumni have returned to the community by bringing various changes and improvements to the lives of the surrounding community. Drugs are narcotics and illegal drugs. Narcotics are classified into two types, namely narcotics in the narrow sense and narcotics in the broad sense. Narcotics in the narrow sense are natural, namely all ingredients of opiaten, cocain, and marijuana. The method of coaching victims of drug abuse in Islamic boarding schools uses: habituation, including: Prayer, reading the Koran, Wirid Method, Sorogan Method, Freedom Method, Supporting factors for Islamic Boarding Schools in fostering victims of drug abuse, among others, namely: 1) Serious intention to improve morals and explore knowledge religion owned by students; 2) Harmonious boarding school atmosphere, full of intimacy between caregivers and students like your own family.